Influence of playing standard on the physical demands of junior rugby league tournament match-play - Gabbett, T. J. (Journal of Science and Medicine in Sport, 2014)
Objectives: To investigate the physical demands on junior rugby league players competing at three different standards of tournament match-play. Design: Cross-sectional study. Methods: Sixty junior rugby league players (mean ± SD age, 16.7 ± 0.7 years) participated in this study. Players were either competing in Division 1, Division 2, or Division 3 teams of the Confraternity carnival. Global positioning system (GPS) analysis was completed during 17 matches (totalling 139 appearances). Results: Division 1 and 2 players covered significantly (p = 0.001) greater distance per minute of match play than Division 3 players (83.0 ± 12.3 m/min and 81.5 ± 6.9 m/min vs. 73.3 ± 9.8 m/min). The greater total distance at the higher competitive standard was achieved through greater (p = 0.001) distances at low speeds, with Division 1 players also covering more (p = 0.038) high speed running than Division 3 players. Expressed relative to playing time, the number of total collisions was lower (p = 0.001) in Division 3 players. Division 2 players engaged in more (p = 0.034) repeated high-intensity effort bouts than Division 3 players. Significant decrements in total (p = 0.005) and low speed distances (p = 0.006) were found, with Division 3 players showing the largest reductions in performance. Conclusions: These findings demonstrate that both the average intensity and the repeated high-intensity effort demands of junior rugby league tournament match-play are greater at higher playing standards. Sport scientists and conditioning staff can use these data to plan appropriate training sessions to allow players to tolerate match-play demands, and recover from the demands of competition.